BTLA (C272) expression on CD4+ T cells in Behçet patients - Ilhan, Fulya; Demir, Nesrin; Demir, Tamer; Gödekmerdan, Ahmet (My University, 2012)
Aim: To investigate the peripheral blood levels of B and T lymphocyte attenuator (BTLA/CD272) on T cells and its role in Behçet disease (BD), and to define the role of inhibitory receptors on BD. Materials and methods: Included in this study were 25 patients with BD and 20 healthy control subjects, matched for age and sex. Results: CD4+CD272+ (P < 0.001) and CD3+CD272+ (P < 0.001) T cell levels were significantly higher in BD patients (active and remission) compared to the healthy controls. However, there was no difference between the active patients and those in remission in terms of CD4+CD272+ T cells, while CD3+CD272+ T cell levels were significantly higher in active-phase BD patients compared to patients in the remission phase (P < 0.05). Conclusion: Further functional studies could be implemented to investigate the effectiveness of the present research parameter in the diagnosis or follow-up of certain diseases similar to BD and with obscure etiology, as well as its contribution to immune dysregulation of BD. BTLA can additionally modulate T cell response in BD on different inflammatory areas and it can be upregulated in BD because of T cell activation. The results of the present study indicate that BTLA expression on CD4+ Th (T helper) cells might play a limiting role on the inflammation at peripheral sites or organs in BD.
Keywords: Genel ve Dahili Tıp; İmmünoloji